Swedish Trends in Criminal Assaults against Minors since Banning Spanking, 1981-2010 - Larzelere, Robert E.; Swindle, Taren; Johnson, Byron R. (International Journal of Criminology and Sociology, 2013)
This study uses Swedish trends in alleged criminal assaults against minors to investigate whether societal violence has decreased since their spanking ban in 1979.The rates of all assaults increased dramatically. Compared to 1981, criminal statistics in 2010 included about 22 times as many cases of physical child abuse, 24 times as many assaults by minors against minors, and 73 times as many rapes of minors under the age of 15. Although the first cohort born after the spanking ban showed a smaller percentage increase in perpetrating assaults against minors than other age cohorts, those born since the spanking ban had almost a 12-fold increase in perpetrations altogether, compared to a 7-fold increase for older age cohorts. Although some increases might reflect changes in reporting practices, their magnitude and consistency suggest that part of these increases are real. Recent increases may be due to expanding proscriptions against nonphysical disciplinary consequences. Future research needs to identify effective alternative disciplinary consequences to replace spanking. Otherwise, proscriptions against an expanding range of disciplinary consequences may undermine the kind of appropriate parental authority that can facilitate the development of impulse control in oppositional children and appropriate respect for others, especially the physically vulnerable